Philosophy and Pedagogy. Can Pedagogy Exist Without Normativity? - Leś, Tomasz (INSTED: Interdisciplinary Studies in Education & Society, 2011)
This article is an attempt to answer the question about scientific status of pedagogy; is it only empirical or empirical and normative discipline? The answer to that question is, at the same time, the answer to the question about relations between pedagogy and philosophy. I argue (using a few argument strategies) that pedagogy is an empirical and normative science; it means that there is no pedagogy without philosophy.